Dampak status sosial ekonomi terhadap motivasi belajar siswa kelas VI sekolah dasar pada mata pelajaran ilmu pengetahuan alam dan sosial - Moch Rifa'i; Nabila Fitria Azro; Muhammad Edy Nurtamam (Universitas Sebelas Maret, 2025)
This study aims to analyze the impact of socioeconomic status on students' learning motivation at SDN Banyuajuh 3 Kamal. The research employs a descriptive qualitative approach with a case study design. The sample consists of sixth-grade students from diverse economic backgrounds and IPAS subject teachers. Data collection techniques include observing students' engagement in learning activities, conducting semi-structured interviews with teachers and students, and analyzing relevant documents. Data validity is ensured through source and method triangulation. The collected data is analyzed using a descriptive qualitative technique, involving data reduction, data presentation, and conclusion drawing. The findings reveal that students from lower economic backgrounds tend to be more passive in IPAS learning, particularly in exploratory activities such as experiments and class discussions. However, teaching strategies, peer support, and parental involvement also play significant roles in enhancing students' motivation. Teachers who implement project-based and exploratory learning methods can effectively increase student engagement, including those from disadvantaged backgrounds. Additionally, peer support and effective communication with parents have been proven to foster students' participation. This study recommends implementing more inclusive and collaborative teaching strategies to enhance students' learning motivation regardless of economic factors